22. THE COMPLIANCE OF ROUTINE HAND HYGIENE AMONG HEALTHCARE WORKERS AT YEN SON DISTRICT HEALTH CENTER, TUYEN QUANG PROVINCE, IN 2023 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2023)
Objective: The study described the routine hand hygiene of healthcare workers at Yen Son District Health Center in 2023 and some associated factors. Research method and time: This was a cross-sectional study. There were 246 chances for hand hygiene to be observed using a checklist. The implementation period of the study was from January 2023 to the end of March 2023. Data were analyzed by SPSS software version 16.0. Chi-square and odd ratios were applied with a significant level at 0.05. Results: The prevalence of routine hygiene compliance was 87.8%. The prevalence of routine hygiene compliance was 32% among nurses; the lowest was among midwives (11.1%). There was a relationship between knowledge and healthcare workers’ compliance with routine hand hygiene. This difference was significant with p
Keywords: Routine hand hygiene; Yen Son District Health Center; healthcare workers.